Polymorphism In Ifngr2 Gene And Its Association With Susceptibility To Tuberculosis In Cattle - Bhaladhare, Ashish; Kumar, Amit; Quadari, M.A.; Sharma, Deepak (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A total of 245 indigenous cattle were screened for presence of bovine tuberculosis by using Single Intradermal tuberculin test. A resource population (35 Case and 49 Control animals) was developed. Polymorphism at one non-synonymous Single nucleotide polymorphism (SNP) locus from exonic region of IFNGR2 gene i.e. IFNGR2-C277T was studied by using Polymoerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP). Polymorphic PCR-RFLP pattern with HpaII in the resource population showed the existence of the SNP site in indigenous cattle also. Low level of polymorphism as well as heterozygocity was observed at this SNP. The frequency of C allele was 0.686 in case and 0.694 in control whereas T allele had frequency of 0.314 and 0.306 in case and control population respectively. Similarly the frequency of genotype CC, TC and TT were 0.486, 0.400, and 0.114 in case and 0.531, 0.326, and 0.143 respectively in control. The probability values showed that the genotype (P = 0.77) as well as allele (P = 0.91) had non significant effect on occurrence of bovine tuberculosis.
Keywords: Tuberculosis; Cattle; IFNGR2; genetic polymorphism